Komórki glejowe Müllera – mediatorzy zaburzeń naczyniowych z patologią złącza szklistkowo-plamkowego w makulopatii cukrzycowej - Robaszkiewicz, Jacek; Chmielewska, Katarzyna; Figurska, Małgorzata; Wierzbowska, Joanna; Stankiewicz, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
The key to identifying the type of diabetic maculopathy is determining the status of posterior vitreous adhesion. In the pathological state, the breakdown of the internal and external blood-retina barrier is evident, however the mechanism is usually complex. The common denominator for these disorders are Müller glial cells, which mediate in maintaining the blood-retina barrier by linking the vessels, neurons and the vitreous in anatomical network and into functional dependence. The breakdown of the blood-retina barrier results in proliferation of Müller cells. Molecular changes in these cells increase endothelial barrier properties, but also induce pathological processes on the vitreo-retinal junction, resulting in increased adhesiveness of the collagen fibers of vitreous to retinal internal limiting membrane. The ability of Müller cells to reactive gliosis is influenced by the healthy functioning of the retinal pigment epithelium, which is a source of trophic factors necessary for appropriate Müller cells morphogenesis. Vitrectomy with the removal of ILM eliminates the vitreofoveal interface pathology, additionaly provoking reactive gliosis within the macula. Intraoperative use of anti-VEGF supports short-term tightness of the blood-retina barrier in the perioperative neuralgic period. In the future, supplying astrocytes may be a strategy that will allow not only the inhibition of pathological neovascularization but also the restoration of the physiological network of capillaries in avascular retina areas. The delivery of recombinant PEDF allows for the recovery of Müller cells, and thus creates the conditions favourable for the survival of nerve cells in loss of retinal homeostasis.